The UHPLC-UV method applied for the forced degradation study of ixazomib and HRMS identification of its degradation products - Hatokova, Paulina; Sestak, Vit; Piskackova, Hana Bavlovic; Melnikova, Iuliia; Roh, Jaroslav; Sterbova-Kovarikova, Petra (Journal of pharmaceutical and biomedical analysis, 2023)
Ixazomib is the only orally active proteasome inhibitor used in clinical practice as an anticancer drug. The novel, rapid UHPLC-UV assay for ixazomib was developed and applied to the forced degradation study followed by HRMS identification of the main degradation products. Oxidative deboronation and hydrolysis of the amid bond were found to be the principal degradation pathways. The chemical standards of the main degradation products were prepared. The method was validated for the simultaneous assay of ixazomib and its degradation products within the concentration ranges of 2.50-100.00 μg/mL (ixazomib); 0.75-60.00 μg/mL (Impurity A and B) and 1.25-60.00 μg/mL (Impurity C). The stability study revealed that ixazomib in solution is: 1) relatively stable in neutral and acidic environments, 2) its decomposition is accelerated at higher pH, 3) it is sensitive to the effects of oxidants and light, and 4) the degradation of ixazomib follows the first-order kinetics under neutral, acidic, alkaline, and UV stress. Contrary, the solid substance of ixazomib citrate was relatively resistant to heat (70 °C), heat/humidity (70 °C/75 % RH), and UV irradiation for 24 h. This study presents the first MS-compatible UHPLC method for the quantification of ixazomib and its degradation products. Furthermore, it provides data about the inherent stability and kinetics of degradation of ixazomib in a solution that may be useful in further investigation of this drug, or the development of novel proteasome inhibitors based on the ixazomib structure.
Keywords: glycin; Antineoplastic Agents; sloučeniny boru; stabilita léku; Chromatography, High Pressure Liquid; Proteasome Inhibitors; hydrolýza; protinádorové látky; oxidace-redukce; Boron Compounds; Drug Stability; Oxidation-Reduction; inhibitory proteasomu; Hydrolysis; vysokoúčinná kapalinová chromatografie; Glycine